THE EFFECT OF IMAGE MEDIA AND BUDDHIST SONGS ON LEARNING OUTCOMES OF BUDDHA RELIGIOUS EDUCATION - Hariyanto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the differences of students’ learning outcomes by using Buddhist pictures and songs as compared to learning through material presentation by teachers using textbooks . The research design used the Nonequivalent Control Group Design. The research subjects were third grade students of Buddhist elementary schools in Wonogiri Regency. The normality test used the One- Sample Kolmogorov-Smirnov Test and the homogeneity test used the Levence Test on SPSS. Meanwhile, to test the hypothesis used the Independent Sample T Test and Paired Sample T Test on SPSS. The results showed that the learning outcomes of the experimental group and the control group were normally distributed and homogeneous. The average increased in learning outcomes of the control group was 5.1250, while the experimental group was 16.5000. The results of the independent sample t test showed that Sig. (2-tailed) or p 0.000, while α 0.05, so p <α meant that Ho was rejected. The results of the paired sample t test were known to be sig. (2-tailed) or p 0.000, while α 0.05 so p <α meant that Ho was rejected. It meant that Buddhist images and songs have a more positive effect on learning outcomes.